Apartheid urban development and transitional restructuring in Pietersburg and environs (Historia, 2021)
Effects of urban development on former homelands need to be addressed after the period of urban transition. The article focuses on the evolution of a dispersed city settlement around Pietersburg. Three aspects are covered. Firstly, an outline is given of the apartheid legacy of developing a dispersed settlement system surrounding Pietersburg. Secondly, the post-apartheid local government restructuring of Pietersburg is described. Thirdly, the above historical findings are debated in the context of 'restructuring' Pietersburg after the transition to a new dispensation.
Keywords: Homeland legacies; Lebowakgomo; Negotiation Forums; Lebowa; Seshego; Transitional restructuring; Mankweng; Ethnic towns; Pietersburg settlements; Urban transition; Apartheid politics; History